Ecological plasticity governs ecosystem services in multilayer networks - Gray, Clare; Ma, Athen; McLaughlin, Orla; Petit, Sandrine; Woodward, Guy; Bohan, David A. (Communications biology, 2021)
Agriculture is under pressure to achieve sustainable development goals for biodiversity and ecosystem services. Services in agro-ecosystems are typically driven by key species, and changes in the community composition and species abundance can have multifaceted effects. Assessment of individual services overlooks co-variance between different, but related, services coupled by a common group of species. This partial view ignores how effects propagate through an ecosystem. We conduct an analysis of 374 agricultural multilayer networks of two related services of weed seed regulation and gastropod mollusc predation delivered by carabid beetles. We found that weed seed regulation increased with the herbivore predation interaction frequency, computed from the network of trophic links between carabids and weed seeds in the herbivore layer. Weed seed regulation and herbivore interaction frequencies declined as the interaction frequencies between carabids and molluscs in the carnivore layer increased. This suggests that carabids can switch to gastropod predation with community change, and that link turnover rewires the herbivore and carnivore network layers affecting seed regulation. Our study reveals that ecosystem services are governed by ecological plasticity in structurally complex, multi-layer networks. Sustainable management therefore needs to go beyond the autecological approaches to ecosystem services that predominate, particularly in agriculture. Clare Gray et al. construct multilayer networks of weed seed regulation and pest gastropod predation by carabid beetles in 374 agricultural fields and show that these ecosystem services are mediated by trophic interaction frequencies. This study reveals that ecosystem services are governed by ecological plasticity in structurally complex, multi-layer trophic networks and these could assist in the assessment of the contribution of biodiversity to ecosystem services.